La mostra "Fiorentina Primaverile" del 1922 Ricostruzione filologica dell'esposizione e del dibattito critico - GRECO, EMANUELE (Premio Ricerca «Città di Firenze», 2020)
Inaugurated in Florence in 1922, the "Fiorentina Primaverile" was an important exhibition of Italian contemporary art, conceived by the writer Sem Benelli. This exhibition remains unique to Florence because of the number (more than three hundred) and the importance of the participants (from Andreotti and Wildt, to Conti and Bacci; from macchiaioli masters like Lega and Signorini to the young artists of «Valori Plastici») as well as for the moment when it took place: a fruitful period for artistic events, like the great exhibition of the Italian Paintings from the 17th and 18th Centuries. Analyzing the archival documents of the exhibition, that have been unpublished until now, this text aims to reconstruct in a historical and critical manner, for the first time, the "Fiorentina Primaverile", in order to identify the true nature of the exhibition and, most of all, which kind of idea of Italian contemporary art was intended to be offered to the public.